In vitro Assessment of the Probiotic Properties and Bacteriocinogenic Potential of Pediococcus pentosaceus MZF16 Isolated From Artisanal Tunisian Meat “Dried Ossban” - Zommiti, Mohamed; Bouffartigues, Emeline; Maillot, Olivier; Barreau, Magalie; Szunerits, Sabine; Sebei, Khaled; Feuilloley, Marc; Connil, Nathalie; Ferchichi, Mounir (Frontiers in Microbiology, 2018)
Pediococcus pentosaceus MZF16 has been isolated from artisanal Tunisian meat so called “Dried Ossban,” an original ecological niche, and identified by MALDI-TOF mass spectrometry and 16S rDNA sequencing. This bacterium showed a high tolerance to gastric stress conditions, and toward bile salts. P. pentosaceus MZF16 also demonstrated a hydrophobic surface profile (high adhesion to xylene), autoaggregation, and adhesive abilities to the human intestinal Caco-2/TC7 cell line. These properties may help the bacterium colonizing the gut. Furthermore, MZF16 was found to be resistant to gentamycin and chloramphenicol but did not harbor any transferable resistance determinants and/or virulence genes. The data also demonstrated absence of cytotoxicity of this strain. Conversely, P. pentosaceus MZF16 can slightly stimulate the immune system and enhance the intestinal epithelial barrier function. Moreover, this bacterium has been shown to be highly active against Listeria spp. due to bacteriocin production. Characterization of the bacteriocin by PCR amplification, sequencing and bioinformatic analyses revealed that MZF16 produces a bacteriocin 100% identical to coagulin, a pediocin-like inhibitory substance produced by Bacillus coagulans. To our knowledge, this is the first report that highlights the production of a pediocin 100% identical to coagulin in a Pediococcus strain. As coagulin, pediocin MZF16 has the consensus sequence YYGNGVXCXXXXCXVXXXXA (X denotes any amino acid), which confirms its belonging to class IIa bacteriocins, and its suitability to preserve foods from Listeria monocytogenes development. According to these results, P. pentosaceus MZF16 can be proposed as a probiotic and bioprotective agent for fermented foods, including Tunisian dry meat and sausages. Further investigations will aim to study the behavior of this strain in meat products as a component of functional food.